2014
DOI: 10.1371/journal.pone.0089205
|View full text |Cite|
|
Sign up to set email alerts
|

Corneal Alterations Induced by Topical Application of Commercial Latanoprost, Travoprost and Bimatoprost in Rabbit

Abstract: Prostaglandin (PG) analogs, including latanoprost, travoprost, and bimatoprost, are currently the most commonly used topical ocular hypotensive medications. The purpose of this study was to investigate the corneal alterations in rabbits following exposure to commercial solution of latanoprost, travoprost and bimatoprost. A total of 64 New Zealand albino rabbits were used and four groups of treatments were constituted. Commercial latanoprost, travoprost, bimatoprost or 0.02% benzalkonium chloride (BAK) was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
4
6
0
1
Order By: Relevance
“…Anatomically, the cornea and iris of treated mice were relatively unaffected by sustained latanoprost treatment. Consistent with findings from other studies 54 , long-term treatment with the preservative present in commercial latanoprost, BAK, leads to corneal thinning. In comparing our findings to those from clinical studies conducted in humans, we noted both similarities and differences, all of which are relevant to ongoing studies of ophthalmic drug development and glaucoma.…”
Section: Discussionsupporting
confidence: 91%
“…Anatomically, the cornea and iris of treated mice were relatively unaffected by sustained latanoprost treatment. Consistent with findings from other studies 54 , long-term treatment with the preservative present in commercial latanoprost, BAK, leads to corneal thinning. In comparing our findings to those from clinical studies conducted in humans, we noted both similarities and differences, all of which are relevant to ongoing studies of ophthalmic drug development and glaucoma.…”
Section: Discussionsupporting
confidence: 91%
“…Since the tear meniscus height and TBUT did not show any significant change, the role of superficial punctate keratitis, or SPK, improvement might not be due to an increase in tear volume but to alleviation of drug-induced cytotoxicity and/or tear film formation. Chen et al reported that commercial latanoprost, travoprost, and bimatoprost damaged the corneal epithelium by breaking down the barrier integrity, cell junction, and cytoskeleton but did not affect aqueous tear production or the TBUT [ 18 ], which is consistent with the current results. Lee et al also reported no significant difference in the TBUT and Schirmer's test between chronically medicated patients and patients who underwent trabeculectomy [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…ZO-1 and occludin-1, as markers of corneal epithelial tight junction, are expressed in the superficial cell layer of the corneal epithelium. 5 In this study, immunofluorescent staining showed topical latanoprost eye drops treatment resulted in loss of ZO-1 in the superficial corneal epithelial cellular border (Fig. 2C), and qRT-PCR showed that topical latanoprost eye drops treatment significantly decreased the mRNA levels of ZO-1 and occludin-1 in corneal epithelium at day 7 (Figs.…”
Section: Topical Application Of Latanoprost Eye Drops Disrupted Cornesupporting
confidence: 54%
“…A growing body of clinical and experimental studies revealed that long-term use of latanoprost eye drops may lead to tear film instability; epithelial apoptosis; corneal epithelial barrier disruption; conjunctival inflammation; and ocular discomfort including burning, stinging, pain, and foreign body sensation. [4][5][6][7] Latanoprost eye drops usually contain a preservative, which is generally considered to be the major factor responsible for ocular surface side effects. Preservatives used in latanoprost eye drops, such as benzalkonium chloride (BAC), may cause or aggravate dry eye disease through various mechanisms such as its toxic and proinflammatory effects as well as detergent properties, which have been well demonstrated in numerous experimental and clinical investigations.…”
mentioning
confidence: 99%